2016
DOI: 10.1016/j.soildyn.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain stochastic finite element simulation of uncertain seismic wave propagation through uncertain heterogeneous solids

Abstract: This paper presents an efficient numerical methodology in probabilistically solving the governing partial differential equation of solid mechanics with uncertainties in both the material parameter and forcing function in the time domain using the stochastic Galerkin approach. The methodology hypothesizes the input forcing function and the elastic modulus of the solid to be a nonstationary random process and a heterogeneous random field, respectively, and efficiently represents them in terms of multidimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Although the stochastic Galerkin method requires modification/redevelopment of the deterministic program, it can be shown that intrusive stochastic Galerkin method is advantageous over non-intrusive approaches in terms of computational efficiency (Xiu 2010). Recently, a time-domain intrusive stochastic elastic-plastic finite element method was developed by Sett et al (2011), Wang and Sett (2016) using stochastic Galerkin method. Developed methodology can incorporate non-Gaussian random field for uncertain material parameters and non-stationary random process for uncertain seismic loads, and perform stochastic seismic wave propagation analysis (Wang and Sett 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the stochastic Galerkin method requires modification/redevelopment of the deterministic program, it can be shown that intrusive stochastic Galerkin method is advantageous over non-intrusive approaches in terms of computational efficiency (Xiu 2010). Recently, a time-domain intrusive stochastic elastic-plastic finite element method was developed by Sett et al (2011), Wang and Sett (2016) using stochastic Galerkin method. Developed methodology can incorporate non-Gaussian random field for uncertain material parameters and non-stationary random process for uncertain seismic loads, and perform stochastic seismic wave propagation analysis (Wang and Sett 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Manktelow et al [5] proposed a perturbation analysis by using discretization finite element method to research wave motion in continuous and periodic structures. Wang and Sett [6] used the stochastic Galerkin method, where material parameters and mechanical functions are uncertain to solve the solid mechanics partial differential equation. Gravenkamp et al [7] resolved the results of high frequencies wave motion by using the following methods: scaled boundary finite element method and the nonuniform rational B-splines.…”
Section: Introductionmentioning
confidence: 99%
“…Darvini (2016) has analyzed the impact of the boundary conditions on flow and transport solutions for the case of a two-dimensional heterogeneous medium based on the stochastic FEM. Wang and Sett (2016) have presented an efficient numerical methodology in probabilistically solving the governing partial differential equation of solid mechanics using the stochastic FEM. Especially, some research has been conducted on the impacts of geotechnical material randomness on dam structural response.…”
Section: Introductionmentioning
confidence: 99%